Inhibition of CXXC5 function rescues Alzheimer's disease phenotypes by restoring Wnt/β-catenin signaling pathway - Minguen Yoon; Heejene Kim; Heewon Shin; HeeYang Lee; Min-Jeong Kang; Sung-Hye Park; Gyoonhee Han; YoungSoo Kim; Kang-Yell Choi (Elsevier, 2023)
Alzheimer's disease (AD) is the most prevalent type of dementia and is characterized by cognitive deficits and accumulation of pathological plaques. Owing to the complexity of AD development, paradigms for AD research and drug discovery have shifted to target factors that mediate multiple pathogenesis in AD. Increasing evidence suggests that the suppression of the Wnt/β-catenin signaling pathway plays substantial roles in AD progression. However, the underlying mechanism for the suppression of Wnt/β-catenin pathway associated with AD pathogenesis remains unexplored. In this study, we identified that CXXC5, a negative feedback regulator of the Wnt/β-catenin pathway, was overexpressed in the tissues of AD patients and 5xFAD transgenic mice paired with the suppression of Wnt/β-catenin pathway and its target genes related to AD. The level of CXXC5 was upregulated, upon aging of 5xFAD mice. AD characteristics including cognitive deficits, amyloid-β (Aβ) plaques, neuronal inflammation, and age-dependent increment of AD-related markers were rescued in Cxxc5-/-/5xFAD mice. 5-methoxyindirubin-3'-oxime (KY19334), a small molecule that restores the suppressed Wnt/β-catenin pathway via interference of the CXXC5-Dvl interaction, significantly improved the overall pathogenic phenotypes of 5xFAD mice. Collectively, our findings revealed that CXXC5 plays a key role in AD pathogenesis and suggest inhibition of CXXC5-Dvl interaction as a new therapeutic approach for AD.